Design and Simulation of a Novel Bio-Mechanic Piezoresistive Sensor with Silicon Nanowires - Messina, M.; Njuguna, James A. K.; Dariol, V.; Pace, C.; Angeletti, G. (Cranfield University, 2012)
This paper presents the design of a novel single square millimeter 3-axial accelerometer for head injury detection of racing car drivers. The main requirements of this application are miniaturization and high-G measurement range. We propose a new miniature accelerometer to be incorporated into an earpiece. Nanowires as nanoscale piezoresistive devices have been chosen as sensing element, due to their high sensitivity and miniaturization achievable. By exploiting the electro-mechanical features of nanowires as nanoscale piezoresistors, the nominal sensor sensitivity is overall boosted by more than 30 times. This approach allowssignificant higher accuracy and resolution with smaller sensing element in comparison with conventional devices without the need of signal amplification. This achievement opens up new developments in the area of implanted devices where the high-level of miniaturization and sensitivity is essential.